ANALISIS MAKNA SIMBOLIS TRADISI SEDEKAH BUMI (NYADRAN) DAN PENDIDIKAN ISLAM DI KAPLONGAN LOR, INDRAMAYU - Fuadul Umam (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2020)
The cultural reality of Indonesia, which is diverse in ethnicity, different traditions, as well as religions and traditions that smell of myths is the basis of social and cultural life. The Indonesian nation has long believed in supernatural powers that rule this universe. This is proven by various historical records regarding various kinds of traditional ceremonies and rituals. Some of these supernatural powers are considered beneficial and detrimental. For this reason, it is believed by some that humans always need to strive to soften the hearts of the owners of magical powers by holding ritual ceremonies, pilgrimages, offerings, and vows, including certain artistic performances. The tradition of earth alms (nyadran) in Kaplongan Lor, Karangampel, Indramayu is one of the local wisdoms that combines Hindu-Buddhist and Islamic traditions. The symbolic meaning contained in it makes a positive contribution to Islamic education for the younger generation in the region